The concept and importance of settlement agreements in commercial proceedings (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The article establishes that a settlement agreement in commercial proceedings is a voluntary agreement between the parties to a conflict to resolve a dispute which arose between them in the course of conducting economic activity or in the course of performance of economic contracts. Such an agreement may be concluded both before the dispute is resolved in court and directly during the court proceedings. It is an effective means of dispute resolution, as it avoids lengthy and costly court proceedings and ensures a more prompt resolution of the problem on the merits between the parties to the conflict.It is argued that settlement agreements are an important tool in the economic process, since with their help it is possible to: 1) to save the parties to the dispute on court costs, as well as to save time of courts and judges who are already working in difficult conditions with a significant overload; 2) to maintain normal relations between the parties in conflict. Settlement agreements can help reduce tensions between the parties and increase mutual respect and trust between them; 3) eliminate the risk of uncertainty, as court decisions may not always fully take into account the interests of the parties to the dispute, while settlement agreements usually satisfy the interests of both parties; 4) increase the efficiency of the dispute resolution process, as they can be concluded more quickly than in court. In addition, the conclusion of an agreement allows the parties to resolve the conflict themselves, satisfying each other's interests to the maximum extent possible.It is noted that the legislator has a rather superficial approach to the regulation of conciliation procedures in commercial proceedings, which is a significant gap. In particular, it is important to ensure that the obligations undertaken by the parties to the conflict are compulsory.
Keywords: settlement agreement; dispute; commercial process; court procedure; commercial court.